Design Analysis of Outrigger and Hexagrid System in High Rise Buildings : A Review - Ahirwar, Deepak Kumar; Divya, K.; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2020)
The innovation of high strength structural materials as well as the introduction of predominant development methods gave a lift in the development of tall structures. As the height of the structure increases, they become progressively vulnerable to wind load and seismic load. The opposition of tall structures to lateral loads is the fundamental determinant in the formulation of new basic structural frameworks that develop by the constant endeavors of structural engineers to go on increasing the building height while keeping the deflection inside worthy points of confinement and limiting the measure of materials. In this proposed work an analytical study will be consider on such systems like outrigger system with core shear wall and hex grid systems, so as to determine their structural efficiency in transferring the lateral loads safely to the ground. In this study we are providing review of journals related to analysis of high rise structures.